2017
DOI: 10.1177/0020764017737102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of economic crisis on the social representation of mental health: Analysis of a decade of newspaper coverage

Abstract: These findings suggest that the representation of mental health is multifaceted and may be affected differently in its dimensions. There is a need for stigma-reducing interventions that both account for this complexity and are sensitive to context and period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…In Portugal, 22.9% of adults have met the diagnostic criteria for a mental disorder in the previous year, and these results are similar to other western countries (ALMEIDA & XAVIER 2013). Another reason for the relevance of addressing mental health is the high rates of stigma (NETO et al 2017;STUART & ARBOLEDA-FLÓREZ 2012). The generalization of negative attitudes towards mental illness means that communities will not discuss or convey information on mental health issues.…”
Section: Introductionmentioning
confidence: 57%
“…In Portugal, 22.9% of adults have met the diagnostic criteria for a mental disorder in the previous year, and these results are similar to other western countries (ALMEIDA & XAVIER 2013). Another reason for the relevance of addressing mental health is the high rates of stigma (NETO et al 2017;STUART & ARBOLEDA-FLÓREZ 2012). The generalization of negative attitudes towards mental illness means that communities will not discuss or convey information on mental health issues.…”
Section: Introductionmentioning
confidence: 57%
“…For instance, Washer [13] investigated how severe acute respiratory syndrome (SARS) was depicted in newspapers in the United Kingdom. Dias et al [14] presented a study that analyzed the representations of mental health and its treatment and the impact of the 2008 economic crisis. Ribeiro et al [15] investigated how the Zika outbreak was reported in two major newspapers in Brazil.…”
Section: Prior Workmentioning
confidence: 99%
“…(Islam & Siddique, 2023) (2) This study aimed at analyzing representations of mental health and its treatment and the impact of the 2008 economic crisis. (Dias Neto ,et al, 2017) (3) The results support biased representation in media discourse, in this case Iran's nuclear program. (Atai & Mozaheb, 2013) (4) The articles and images highlight this complex relationship and point to the synthesis brought about by the pressures of competing perspectives by indicating how women both mobilize their rarity value as women in leadership roles to gain representation in the press yet also mobilize their femininity, their 'womanliness', as a resource (Stead, 2013, p. 71), for instance by being photographed in glamorous clothes.…”
Section: Valuementioning
confidence: 91%